The Pigtail Catheter for Pleural Drainage: A Less Invasive Alternative to Tube Thoracostomy - Gammie, James S. (Society of Laparoendoscopic Surgeons, 1999)
BACKGROUND: Tube thoracostomy remains the standard of care for the treatment of pneumothoraces and simple effusions. This report describes a favorable experience with the 8.3 French pigtail catheter as a less invasive alternative to traditional chest tube insertion. METHODS: We retrospectively reviewed 109 consecutive pigtail catheter placements. Catheters were inserted under local anesthesia at the bedside without radiographie guidance. Pre- and post-insertion chest radiographs were reviewed to determine efficacy of drainage. RESULTS: Fifty-one of 109 patients (47%) were mechanically ventilated and 26 patients (24%) had a coagulopathy. There were no complications related to pigtail catheter insertion. Seventy-seven pigtail catheters were placed for pleural effusion and 32 for pneumothorax. Mean effusion volume decreased from 43 to 9 percent, and drainage averaged 2899 ml over 97 hours. Mean pneumothorax size diminished from 38 to 1 percent during an average 71-hour placement. Clinical success rates in the effusion and pneumothorax groups were 86 and 81 percent, respectively. CONCLUSION: The pigtail catheter offers reliable treatment of pneumothoraces and simple effusions and is a safe and less invasive alternative to tube thoracostomy.